A reorganização da direita brasileira e o papel do Movimento Brasil Livre (MBL): da fundação ao impeachment de Dilma Rousseff (2013-2016). - Silva, Kiane Follmann da (2020)
The political metamorphosis experienced in Brazil requires an reorganization process analysis of the right-wing in Brazil, that takes into account the historical reactions of certain classes, and class fractions, to the content of the economic and social policy implemented by governments considered progressive. In general terms, we operate with the central hypothesis that the economic and social policies implemented during the governments of the Workers' Party (PT) reached the reproduction mode of segments of the brazilian middle class, which contributed to the reorganization of the right-wing in the recent period. The emergence of liberal right-wing movements and the public demonstrations that took place from 2013 to 2016, especially Dilma Rousseff's pro-impeachment political mobilizations, show its dissatisfaction and rupture with the government, translating into the recent rise of the right-wing. In this sense, we analyze the Free Brazil Movement (MBL) as one of the political expressions of this rupture, as well as an agglutinating force of middle class segments contrary to PT governm.